Exploring Brannerite-Type Mg1−xMxV2O6 (M = Mn, Cu, Co, or Ni) Oxides: Crystal Structure and Optical Properties - Hua-Chien Hsu; Narayanan Lakshminarasimhan; Jun Li; Arthur P. Ramirez; Mas A. Subramanian (Crystals)
Environmentally benign, highly stable oxides exhibiting desirable optical properties and high near-IR reflectance are being researched for their potential application as pigments. Mg1−xMxV2O6 (M = Mn, Cu, Co, or Ni) oxides with brannerite-type structures were synthesized by the conventional solid-state reaction method to study their optical properties. These series exhibit structural transitions from brannerite (C2/m) to distorted brannerite (P<semantics><mover accent="true">1¯</mover></semantics>) and NiV2O6-type (P<semantics><mover accent="true">1¯</mover></semantics>) structures. The average color of Mg1−xMxV2O6 compounds varies from reddish-yellow to brown to dark brown. The L*a*b* color coordinates reveal that Mg1−xCuxV2O6 and Mg1−xNixV2O6 show more red hues in color with x = 0.4 and x = 0.5, respectively. The UV–Vis diffuse reflectance spectra indicate a possible origin for these results include the ligand-to-metal charge transfer (O2− 2p-V5+ 3d), metal-to-metal charge transfer (from Mn2+ 3d/Cu2+ 3d/Co2+ 3d/Ni2+ 3d to V5+ 3d), band gap transitions, and d–d transitions. Magnetic property measurements revealed antiferromagnetic behavior for the compounds Mg1−xMxV2O6 (M = Mn, Cu, Co, and Ni), and an oxidation state of +2 for the M ions was deduced from their Curie–Weiss behavior. The system Mg1−xMnxV2O6 has a NIR reflectance in the range between 40% and 70%, indicating its potential to be utilized in the pigment industry.